Let x1 and x2

==> x1+x2 = 3.......(1)

==> x1^3+ x2^3 = 63.......(2)

from (2)

==> x1^3 + x2^3 = (x1+x2)^3 - 3ab(a+b)

==> 63 = 3^3 - 3ab(3)

==> 63 = 27 - 9ab

==> 36 = -9ab

==> ab = 36/-9 = -4

Now we know that the sum =...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Let x1 and x2

==> x1+x2 = 3.......(1)

==> x1^3+ x2^3 = 63.......(2)

from (2)

==> x1^3 + x2^3 = (x1+x2)^3 - 3ab(a+b)

==> 63 = 3^3 - 3ab(3)

==> 63 = 27 - 9ab

==> 36 = -9ab

==> ab = 36/-9 = -4

Now we know that the sum = 3

and the product = -6

==> The equation is:

**x^2 - 3x - 4 = 0**